Advantages and disadvantages of the project management method - Sevinch Tolliboyeva is Nuriddin's daughter (Global Scientific Publishing, 2024)
Project management is a widely used method for organizing and executing tasks in a systematic manner. It involves the process of planning, organizing, and controlling resources to achieve specific goals and objectives within a specified time frame. While project management has several advantages, it also comes with its own set of disadvantages.
Keywords: management; several advantages; planning